511Effects of educational activities prior to school entry are more important for socioeconomically disadvantaged children. (2nd September 2021) - Gialamas, Angela; Haag, Dandara; Mittinty, Murthy; Lynch, John
Abstract: Background: We examined whether time in educational activities at 2-3 years and language ability at school entry differed among children from diverse socioeconomic backgrounds. Methods: Data were drawn from the Longitudinal Study of Australian Children (n = 4253). Educational activities were collected using time-use diaries. Household income was measured using parent self-report. Language ability was assessed using the Peabody Picture Vocabulary Test. Marginal structural models with inverse probability of treatment weights were used to assess modification of the effect of time spent in educational activities on language ability by income. Results: Children exposed to both <30 minutes/day in educational activities and being in a low-income household were at greater risk of poorer outcomes than the simple sum of their independent effects. Compared with children who spent ≥30 minutes/day in educational activities and from higher-income households, children who experienced <30 minutes/day from low-income households had a 2.30 (95% CI: 1.88, 2.80) higher risk of having lower language ability. The Relative Excess Risk Due to Interaction of 0.15 (95% CI:-0.15, 0.67) was greater than zero indicating a super-additive effect measure modification by income. Conclusions: Our results suggest that boosting time in educational activities to 30 minutes/day would benefit the lower-income group relatively more than the higher-income group. Key messages: If there was an intervention of sufficient dose to increase the amount of time spent in educational activities to 30 minutes/day for children in the lower-income group, the risk of children having lower language ability at school entry could be reduced by 45%.